Musculoskeletal pain and work absence - a 10 year follow-up study of Norwegian young adult twins - Ragnhild E. Ørstavik; Gun Peggy Knudsen; Kristian Tambs; Line C. Gjerde; Fartein Ask Torvik; Christopher Nielsen; Espen Røysamb; Ted Reichborn-Kjennerud (Norsk Forening for Epidemiologi, 2016)
Background and aims: Sickness absence (SA) and disability pension (DP) are increasingly recognized as major public problems. Musculoskeletal disorders are among the most common diagnoses set by physicians granting SA and DP. Results from recent twin studies have established that SA and DP are influenced not only by environmental and social factors, but also moderately to substantially by genes. The aim of the current study was to examine to what degree musculoskeletal complaints in young adults predict SA and DP, including SA granted for other diagnoses. As the participants were twins, we were able to perform within pair analyses, to see if the associations between musculoskeletal pain and later DP or SA were confounded by unmeasured genetic and shared environmental factors. Materials and methods: The Norwegian twin registry includes a questionnaire conducted in 1998. From this, we included three measures of recurrent pain (lower back, neck/shoulders and muscular) as well as symptoms of anxiety and depression (measured by the Symptom Checklist-5 (SCL-5)). The questionnaire has been linked to highly reliable official registries on SA and DP, as well as a range of sociodemographic variables, for a ten-year follow up period. We applied logistic (DP as dependent variable) and binomial regression (SA as dependent variable) analyses to explore the relationship between musculoskeletal pain and DP and SA. In the final models, we adjusted for sociodemographic factors and symptoms of anxiety and depression. Differences between twins in a pair were explored by applying fixed effect models. All analyses were conducted using STATA version 13.1. Results: The final sample of 7,626 twins included 3,055 complete pairs (488 monozygotic (MZ) male, 349 dizygotic (DZ) male, 747 MZ female, 589 DZ female, and 882 opposite sex twin pairs) and 1,516 singletons. By the end of follow up, 181 subjects (44 men and 137 women) received DP, and 63.7% of the sample (47.4% of males and 76.0% of females) had at least one period of SA extending 16 days. Pain at any site was significantly associated with DP in both sexes. Any increase in the number of pain sites reported was associated with about a 60% increased risk for receiving DP (OR 1.6, 95% CI 1.4-1.9), and the strength of the association was only marginally reduced when adjusted for symptoms of mental disorders (1.4, 1.2- 1.7). In the within pair analyses the effect was no longer significant, indicating possible confounding from genetic and shared environmental effects. As for all cause SA, musculoskeletal pain predicted SA independently of all measured confounders, and the results remained significant in the within pair analyses (Incidence Rate Ratio (IRR) 1.12, 95% CI 1.03-1.23). Conclusion: In young adults, musculoskeletal pain strongly predicted SA and DP for a 10 year follow-up period. Musculoskeletal pain was associated with higher levels of all cause SA, even within discordant MZ twin pairs. Our results indicate that interventions to prevent musculoskeletal pain in young adults can reduce levels of SA and DP.